PENGARUH DIVIDEND PAYOUT RATIO (DPR), DEBT TO EQUITY RATIO (DER) DAN EARNING PER SHARE (EPS) TERHADAP NILAI PERUSAHAAN PADA SUB SEKTOR INDUSTRIAL GOODS YANG TERDAFTAR DI BURSA EFEK INDONESIA - Aprilia Wulandari Br Lumban Tobing; Hamida Sari Siregar (Smart Education, 2026)
Abstract: This study aims to determine the partial and simultaneous influence of Dividend Payout Ratio (DPR), Debt to Equity Ratio (DER) and Earning Per Share (EPS) on Company Value in the Industrial Goods Sub-Sector listed on the Indonesia Stock Exchange. The number of samples of 10 companies in the 2022-2024 period with a total of 30 observations. Data analysis used multiple linear regression. The results of the t-test, partially of the DPR had a negative effect on the Company's Value with a value -t_hitung of (-3.539) < (-2.05183) t tabel and a significance of 0.002 < 0.05. DER partially had no effect on the Company's Value with a value of 0.026 t hitung < 2.05183 t tabel with a significance value of 0.980 > 0.05. Meanwhile, EPS partially had a negative effect on Company Value with a value -t_hitung of (-3.862) < (-2.05183) and a significance of 0.002 < 0.05. Meanwhile, the results of the F test simultaneously show that the variables DPR, DER and EPS have an effect on the Company's Value with an F value f hitung of 6.144 > 2.98 Ftables and a significance value of 0.003< 0.05. The R2 test, the Adjusted R Square value produced a value of 0.347, meaning that the correlation of all independent variables consisting of Dividend Payout Ratio, Debt to Equity Ratio and Earning Per Share to the dependent variable, namely the company value was 34.7% while the remaining 65.3% was influenced by other factors that were not included in this research model. Keywords: Dividend Payout Ratio, Debt To Equity Ratio, Earning Per Share, Company Values Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh secara parsial dan simultan Dividend Payout Ratio (DPR), Debt To Equity Ratio (DER) Dan Earning Per Share (EPS) Terhadap Nilai Perusahaan Pada Sub Sektor Industrial Goods Yang Terdaftar Di Bursa Efek Indonesia. Jumlah sampel 10 perusahaan pada periode 2022-2024 dengan jumlah pengamatan 30 pengamatan. Analisis data menggunakan regresi linear berganda. Hasil uji t, secara parsial DPR berpengaruh secara negatif terhadap Nilai Perusahaan dengan nilai -t_hitung (-3,539) < -t_tabel (-2,05183) dan signifikansi sebesar 0,002 < 0,05. DER secara parsial tidak berpengaruh terhadap Nilai Perusahaan dengan nilai t_hitung 0,026 < 2,05183 t_tabel dengan nilai signifikansi sebesar 0,980 > 0,05. Sedangkan EPS secara parsial berpengaruh secara negatif terhadap Nilai Perusahaan dengan nilai -t_hitung (-3,862) < -t_tabel (-2,05183) dan signifikansi sebesar 0,001 < 0,05. Sedangkan hasil uji F secara simultan bahwa variabel DPR, DER dan EPS berpengaruh terhadap Nilai Perusahaan dengan nilai Fhitung 6,144 > 2,98 Ftabel dan nilai signifikansi 0,003< 0,05. Uji R2, nilai Adjusted R Square menghasilkan nilai 0,347 artinya korelasi seluruh variabel independen yang terdiri Dividend Payout Ratio, Debt to Equity Ratio dan Earning Per Share terhadap variabel dependen yaitu nilai perusahaan adalah sebesar 34,7% sedangkan sisanya 65,3% dipengaruhi oleh faktor-faktor lain yang tidak dimasukkan dalam model penelitian ini. Kata kunci: Dividend Payout Ratio, Debt To Equity Ratio, Earning Per Share, Nilai Perusahaan